Menuju Super Smart Era 5.0: Tantangan Baru dan Pengembangan Kurikulum Pendidikan Agama Islam - Arya Rahardja, Muhammad Nurfaizi; Rambe, Anggi Afrina; Akmal, Miftahul Jannah; Cevie Putri, Annisa Ningtias; Dwietama, Regita Ayu; Firdaus, Endis (UIR Press, 2024)
This research aims to analyze and explore the challenges related to the problems faced in Islamic religious education in the super smart era 5.0, as well as the development that must be done on the Islamic religious education curriculum in order to be relevant to the super smart era 5.0. This research uses qualitativ method by using descriptiv-analysis technique to analyze and describe the data and findings of this research. Then the approach used is Library research in the study of research and the data source of this research is obtained from various sources of scientific studies such as articles, journals, books, documents, and other data relevant to this research. The results in this study are (1) the development of technology in the super smart era 5.0 provides challenges in the sustainability of Islamic religious education, such as preventing moral degradation in students, preparing educators and students to be able to integrate the use of technology in education, the difficulty of filtering digital content, the influence of social media, the emergence of addictive properties, providing an understanding of the importance of balance between understanding religion and technology, the difficulty of maintaining data security, and (2) the Islamic religious education curriculum must be developed to answer the problems and needs of society, namely by using Tyler's goal-oriented curriculum development model.